Thursday

December 18, 2014

December 18, 2014

Posted by **Math** on Sunday, July 20, 2014 at 3:02pm.

5x - y = 18

–4x – 2y = –6

- Algebra -
**Reiny**, Sunday, July 20, 2014 at 3:19pmI would use substitution, from the 1st:

y = 5x-18

sub into the 2nd:

-4x - 2(5x-18) = -6

-4x - 10x + 36 = -6

-14x = -42

x = 3

y = 5(3)-18 = -3

x=3 , y = -3

**Answer this Question**

**Related Questions**

Algebra - When solving a system of equations by the addition method, how do you ...

Algebra - When solving a system of equations by the addition method, how do you ...

Algebra 2 - 1. What is the first step for solving this system by substitution? ...

Algebra 2 - I need help with this problem because I do not have a graphing ...

Algebra - Explain the difference between solving a linear equation graphically ...

Algebra II - What is the first step for solving this system by substitution? DO ...

Algebra - College intro - I'm having trouble learning "Solving systems of ...

Business Algebra - Produce an example of a system of equations to your fellow ...

Math 116 - Consider the following system of equations. y=2x-2 y-2x=9 What can ...

algebra - Explain the difference between solving a system of equations by the ...